The use of digital technologies in the teaching of mathematics during the COVID-19 Pandemic: a case study with undergraduate tourism students - Pais, S. (2022)
Mathematics is one of the school subjects where demotivation is a frequent concern. Relating mathematics with other areas usually draws students’ attention and increases their involvement in the classes. It is necessary to go beyond the traditional; the teacher must look for resources that make his classes flow, so that the students acquire or increase their interest in mathematics. After the generalized lockdown imposed by the Covid19 pandemic, millions of students and teachers faced new challenges as they progressively come back to their face-to-face school activities. Despite all the constraints caused by the pandemic, this is an opportunity to move towards an innovative and transformative educational model for the future, which must avoid sending us back to the negative aspects of past educational practices. During the lockdown, with face-to-face teaching activities in schools having been suspended and emergency remote teaching (ERT) being put into practice, the teachers involved in this study were faced with the need to adapt activities and didactic materials to be used exclusively at distance with the aid of technology. This included the promotion of asynchronous tasks/activities, which could be developed autonomously by students. Technologies have multiple benefits in the field of Education, such as improving student performance and motivation. Information and Communication Technologies (ICTs) are tools that may be used to innovate the way mathematics is taught and they may facilitate students' learning. Being aware of these benefits, one of the authors of this work decided to adapt and introduce part of the activities and teaching materials prepared for the ERT, in the face-to-face teaching of her classes after lockdown. In order to understand how these changes were perceived by the students, a quantitative survey was conducted. The participants in the study are undergraduate students from a Portuguese higher education institution enrolled in the curricular unit of Statistical Analysis.